Inside Japan's defense : - Chinworth, Michael W. (Brassey's (US), 1992)
Defense analyst Chinworth relates the story of Japan's recent defense industrial development, identifies the Japanese strategy for the year 2000, and demonstrates why and how the US has contributed to Japan's military growth through technology transfers and the protection of their bilateral security